Urogenital epithelial cells as simple markers of estrogen response in infants: methods and applications. - Margaret A Adgent; Gordon P Flake; David M Umbach; Virginia A Stallings; Judy C Bernbaum; Walter J Rogan (PLoS ONE)
Exposure to estrogen-mimicking chemicals during critical periods of development, such as infancy, may have adverse effects. However, these effects can be difficult to characterize in most epidemiologic studies. For example, growth of reproductive organs may be susceptible to estrogenic chemicals, but measuring it requires skilled ultrasound examination; timing of pubertal onset may be altered, but observing it requires long-term follow up. To address the need for a simple marker of response to estrogenic exposures in infants, we propose a novel application of a classic marker of estrogen response in adult women: cytological evaluation of urogenital epithelial cells. In this cross-sectional study of 34 female and 41 male infants, we demonstrate that epithelial cells can be obtained from swabs of the vaginal introitus (females) and urethral meatus (males), as well as from spun urine, and that these cells respond to differential estrogenic conditions, as indicated by the relative abundance of the superficial epithelial cell type. To model varying estrogen exposure, we sampled from infants who were either newborn (highly exposed to maternal estrogens), or 12 weeks old (12 W) (negligibly exposed to estrogen). Newborns had a higher percentage of superficial cells (%S), as compared to 12 W (mean ± standard error: 8.3 ± 1.8 vs. 0.9 ± 0.2) (p < 0.01), consistent with an estrogen response. This difference in %S from newborn to 12 W was observed similarly for swab (-7.6 ± 1.7) and urine (-7.3 ± 2.6) specimens and for males (-9.6 ± 2.9) and females (-5.2 ± 2.1). Examination of urogenital epithelial cells can successfully demonstrate estrogen response in both sexes, using cell specimens collected from either swab or urine sampling. In future studies, this simple, non-invasive method may be applied to assess whether estrogen-mimicking chemicals produce an estrogenic response in infants.